Population of Montserrat : a demographic study - Ebanks, G. Edward (Caricom Secretariat GeorgetownGY, 1985)
Provides an analysis of the 1980 Population Census in Montserrat. Presents information on population size; rate of growth; components of growth; sex composition and spatial distribution. Provides data on age-specific fertility rates; mortality and migration. Examines 3 socio-cultural characteristics of the population viz. education, race and religion. A brief examination of the institution of marriage is given.